(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s
(3ChdgG (B:s
(3cJGH GdJUQja ddRgQGhi ai CeQGV GdeYOI , SJg hYTQhf eQVkG JZjQ eRGL bhGgG hJZjQ eRGLgG Ydi GdLedI hJZjQ eRGLgG ef bHd eTGQcI GdOeGZ hGdJNe, hGdhLY hGdChQGe s
(3BNQgG (B:s
(3BNQ GdfSNI , CUGHJg GdQWhHI , hedMb Hg cdGe ai GdWH ONjd Ydi GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI YGTQIs
(3JJVef ebGdJjf (B: (3GdChdi ai CeQGV GdeYOIs
(3hGdKGfjI ai CeQGV GdMejGJs
(3BNQ GdfSNI eeRb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
Keywords: (3GdWHs